Strategi Dakwah Penyuluh Agama Islam Dalam Peningkatan Pemahaman Praktik Ibadah Kemasyarakatan: (Studi Pada Penyuluh Agama Islam di Kelurahan Lubuk Linggau Ulu Kecamatan Lubuk Linggau Barat 2 Kota Lubuk Llinggau) - Sopiyan, Wawan; Nurjanah, Indah; Mislawati, Sri Eva; Syamsul, Encu M (STAI Bumi Silampari, 2024)
Islamic religious outreach activities by Islamic Religious Counselors play an important role in increasing religious understanding in the Indonesian Islamic community. Even though the number of Islamic religious instructors is still very minimal, changes related to religious understanding in society are considered quite significant and are felt by the community. This research seeks to determine the Islamic Religious Extension Strategy carried out by Islamic Religious Counselors to increase understanding of community worship practices in Lubuk Linggau Ulu Village, Lubuk Linggau Barat 2 District, Lubuk Linggau City. The research was carried out by observing the activities held by Islamic Religious Counselors who provide religious counseling in the Lubuk Linggau Ulu sub-district and conducting in-depth interviews regarding the program of activities carried out. This research uses descriptive qualitative methods. Researchers in observations and interviews found that Islamic Religious Counselors in Lubuk Linggau Ulu Village, Lubuk Linggau Barat 2 District have implemented extension programs, especially programs related to increasing understanding and skills in community worship practices. The results of the research show that Islamic religious instructors in the Lubuk Linggau Ulu sub-district, Lubuk Linggau Barat 2 sub-district are implementing strategies by selecting priority programs, namely programs to increase community understanding, especially in terms of community worship practices because skills in caring for corpses, the knowledge of tajwid and understanding of the fiqh of daily worship are very important. useful and useful in society.